Recurrent facial hemiparesis due to dolichoectatic vertebrobasilar artery: an unusual and ignored cause. (15th March 2013) - Mishra, Vijay Nath; Chaurasia, Rameshwar Nath; Gupta, Shailesh; Joshi, Deepika
Abstract : Dolichoectatic arteries are elongated tortuous aneurysms of intracranial arteries most commonly of vertebrobasilar tree presenting with ischaemic, haemorrhagic, thromboembolic lesions or with cranial nerve compression. The clinical presentation includes tic douloureux, neuralgia, tinnitus, vertigo, motor or sensory deficits, ataxia, dementia, Parkinsonism, hydrocephalus, headache, migraine, aneurysm, neoplasm, stroke/transient ischaemic attacks, leukoencephalopathy, central sleep apnoea and cerebellar dysfunctions. We present a case of recurrent facial nerve palsy secondary to vertebrobasilar dolichoectasia, an interesting and rare condition.